Assessing dam insfrastructure and happiness of rural dwellers : A case of Shiroro Hydro Electricity dam community in Nigeria - Salihu, Musa Ewugi (2015)
Since independence, Nigeria has adopted the central planning approach to development and structural transformation as a deliberate strategy to influence and control the principal sectors of the economy in order to achieve growth and development for the well-being of the citizenry. It was in this spirit that the Shiroro Hydro Electricity Dam was installed in Shiroro village within Niger State in 1990. However, important aspects like the happiness of the host community and the internal security of the installed dam and the likely repercussions such as vandalization of the dam by the host community has often been ignored. The idea behind this research work therefore, is to ascertain the impact of the Shiroro Hydro Electricity Dam on the happiness of the Shiroro community. In order to accomplish this research objective, the study analyzed the socio-economic variables of state of mind, household per capita income, physical environment and social amenities as yardsticks of generating happiness from the treatment and control groups. The study used the Propensity Score Matching technique and the Binary Probit Model to analyze the data. The result obtained indicates that the income level of the community has increased by 18 per cent. However, the community’s happiness status is found to be negative due largely to the loss of farmland, and environmental predicaments like flood and inadequate rural infrastructure amenities. Therefore, the study recommends that the government introduce a flood forecast structure of early warnings to minimize flood damage, introduce farm-education schemes to change the community’s perception of their proneness to local resources opportunities, and introduce a Rural Infrastructure Trust Fund to overcome the social amenity predicament in the community. It is concluded that these support schemes would not only serve as compensation to the dam- created negative externalities but also would go a long way at reducing violence and crime, hence improving the happiness of the host community